2020
DOI: 10.1002/jcp.30216
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic naked mole–rat brains use microRNA to coordinate hypometabolic fuels and neuroprotective defenses

Abstract: Naked mole–rats are among the mammalian champions of hypoxia tolerance. They evolved adaptations centered around reducing metabolic rate to overcome the challenges experienced in their underground burrows. In this study, we used next‐generation sequencing to investigate one of the factors likely supporting hypoxia tolerance in naked mole–rat brains, posttranscriptional microRNAs (miRNAs). Of the 212 conserved miRNAs identified using small RNA sequencing, 18 displayed significant differential expression during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 108 publications
(170 reference statements)
1
16
0
Order By: Relevance
“…In our study, we identified changes in expression of several miRNAs in response to vitrification stress that have also been reported to be involved in the strategies of stress-tolerant animals. Like this, miR-335 has been shown to regulate hypoxiainducible transcription factor 1 in brains of hypoxic naked mole rats (Li et al, 2015;Hadj-Moussa et al, 2021), while in our study it was upregulated in ovarian tissues after vitrification and warming. A study on hibernating grey mouse lemurs reported increased expression of miRNAs miR-92a and miR-193b during torpor, which was related to regulation of p53 signaling and mTOR pathway (Li et al, 2017;Biggar et al, 2018;Zhang et al, 2020).…”
Section: Discussionsupporting
confidence: 50%
“…In our study, we identified changes in expression of several miRNAs in response to vitrification stress that have also been reported to be involved in the strategies of stress-tolerant animals. Like this, miR-335 has been shown to regulate hypoxiainducible transcription factor 1 in brains of hypoxic naked mole rats (Li et al, 2015;Hadj-Moussa et al, 2021), while in our study it was upregulated in ovarian tissues after vitrification and warming. A study on hibernating grey mouse lemurs reported increased expression of miRNAs miR-92a and miR-193b during torpor, which was related to regulation of p53 signaling and mTOR pathway (Li et al, 2017;Biggar et al, 2018;Zhang et al, 2020).…”
Section: Discussionsupporting
confidence: 50%
“…For example, miR-24 that was upregulated in the brain is known to be involved in hypoxia-induced reduction of cytochrome c, a mitochondrial protein involved in inducing apoptosis [ 67 ]. Another study showed that downregulation of miR-335 that regulates the hypoxia-inducible transcription factor-1 (HIF-1) in brains of hypoxic naked mole rats can activate genes involved in glycolysis under low oxygen availability [ 68 , 69 ]. Furthermore, the study showed an upregulation of miR-155 in mole rat brain that targets HIF-1α and also induce the expression of NF-κB transcription factor that is involved in antioxidant defense, DNA damage repair, and the inflammatory response.…”
Section: Microrna Biology From Extreme Animal Survivalists To Human Health and Diseasementioning
confidence: 99%
“…Furthermore, the study showed an upregulation of miR-155 in mole rat brain that targets HIF-1α and also induce the expression of NF-κB transcription factor that is involved in antioxidant defense, DNA damage repair, and the inflammatory response. NF-κB induction can maintain miR-155 levels during hypoxic stress suggesting stringent regulation at a posttranscriptional level by players in the cell stress response machinery [ 69 , 70 ]. A study of hibernating grey mouse lemurs ( Microcebus murinus ) from Madagascar also showed miRNA action in regulating genes involved in cellular defense systems.…”
Section: Microrna Biology From Extreme Animal Survivalists To Human Health and Diseasementioning
confidence: 99%
“…The increase in blood glucose levels may also partly be explained by decreased glucose consumption during hypometabolic states ( Pamenter et al, 2019a ). In the brain, and following acute in vivo hypoxic exposure, mild acidification is observed, lactate dehydrogenase (LDH) protein expression increases, and the expression of SREP2, a key regulator of fatty acid synthesis, decreases ( Hadj-Moussa et al, 2021b ), all consistent with increased glycolytic throughput in this tissue. Finally, NMRs have large cardiac glycogen stores relative to C57/BL5 mice ( Faulkes et al, 2019 ), suggesting this organ is primed for sustained glycolytic metabolism.…”
Section: Introductionmentioning
confidence: 99%